Entrepreneurial Experience and Usage of External Business Support (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Previous studies demonstrate that policy makers and practitioners should target support tailored to special needs of novice and habitual entrepreneurs. This paper aims to present a study of the role of prior business experience in the inclination to use external business support and the choice of various forms of this support. Research were conducted on a sample of 373 Polish small innovative enterprises in the fourth quarter of 2017. Enterprises were surveyed by means of a questionnaire using the CATI (Computer Assisted Telephone Interviewing) technique. The findings suggest that habitual entrepreneurs use external business support to a greater extent than novice entrepreneurs but differences between various forms of support used by novice and habitual entrepreneurs are not significant. The presented research results are a starting point for further detailed analyses that should be undertaken to explore the characteristics of habitual entrepreneurs: whether and to what extent entrepreneurs learn from their own experience, what is the impact of success or failure in previous businesses on the current behaviour of entrepreneurs and their companies, and what implications this brings for the development of the future SME support policy.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.